Green goods in Finland's manufacturing - Natalia Kuosmanen; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2023)
This report examines the production of green goods in Finland's manufacturing sector. Our findings reveal a notable concentration of green products to high-tech industries. While most firms maintain their green product portfolios stable over time, multi-product firms tend to expand their green product portfolios more actively. Large firms stand out with active management of their green goods portfolios, discontinuing some green products while introducing new ones. Additionally, we examine firm characteristics that associate with firms' engagement in the production of green goods. We find a positive correlation between production of green products and factors such as labor productivity, product diversity, and multi-industry operations.
Keywords: C23; L60; O44; Q54; Q55; Q56; 330; Environmental goods; Green products; Firm renewal; Manufacturing industries